PEMBUKAAN HUTAN SEBAGAI HUNIAN PERSPEKTIF HUKUM ISLAM - Luthfi Alviansyah; M. Agung Izzul Haq (Media Keadilan: Jurnal Ilmu Hukum, 2022)
This research departs from concerns with the current conditions, namely the rampant large-scale forest clearing to be used as new settlements or dwellings regardless of forest sustainability. Utilization and clearing of forests to be used and built as dwellings is a form of forest utilization. Meanwhile, Islamic law is a legal system that applies and is applied in Indonesia apart from customary law and continental European law (civil law). This research is a type of qualitative research carried out through a normative juridical approach using an analytical descriptive method based on the results of library research. Based on research, it is known that first, the concept of Islamic law about, the forest is placed as Al-Mubahat which is an ecosystem area that is free when it enters the Al-Mawat group (dead earth status) which is located in the wild forest, and is said to be Marafiq Al-Balad where it has the status of a fringe earth if the forest area is located around a residential area. Both types of forests are the responsibility of the government which has the authority to grant forest management permits by paying attention to the impacts that occur so as not to harm the surrounding environment. Second, this type of forest is the responsibility of the government which has the authority to grant forest management permits by paying attention to the impacts that occur so as not to harm the surrounding environment. Secondly, humans are in principle allowed to use forests for the purposes of their lives provided that the utilization carried out is not excessive and also does not harm the environment and nature.Keywords: Forest clearing; Forest protection; forest management; Islamic Law Perspective.ABSTRAKPenelitian ini berangkat dari keprihatinan dengan kondisi yang terjadi saat ini, yaitu maraknya pembukaan hutan secara besar-besaran guna dijadikan pemukiman atau hunian baru tanpa memerdulikan kelesatarian hutan. Pemanfaataan dan pembukaan hutan untuk digunakan dan dibangun sebagai hunian merupakan salah satu bentuk pemanfaatan hutan. Sementara hukum Islam merupakan sistem hukum yang berlaku dan diterapkan di Indonesia selain daripada hukum adat dan hukum eropa kontinental (civil law). Penelitian ini merupakan jenis penelitian kualitatif yang dilakukan melalui pendekatan yuridis normatif dengan menggunakan metode deskriptif analistis berdasarkan hasil riset kepustakaan (library research). Berdasarkan penelitian diketahui bahwa pertama, konsep hukum Islam tentang, hutan ditempatkan sebagai Al-Mubahat dimana merupakan suatu wilayah ekosistem yang bebas apabila masuk ke dalam golongan Al-Mawat (status bumi mati) yang terletak pada hutan liar, dan dikatakan sebagai Marafiq Al-Balad dimana berstatus bumi pinggiran apabila kawasan hutan tersebut terletak pada sekitar area pemukiman. Kedua jenis hutan tersebut menjadi tanggung jawab pemerintah yang memiliki kewenangan dalam pemberian izin pengelolaan hutan dengan memperhatikan dampak yang terjadi supaya tidak merugikan lingkungan sekitar. Kedua, manusia pada prinsipnya diperbolehkan untuk memanfaatkan hutan untuk keperluan hidupnya dengan ketentuan bahwa pemanfaatan yang dilakukan tidak berlebihan dan juga tidak merusak lingkungan dan alam.